1) Evaluate the function f(x)=-3x+7

   a) Find f(2)

   b) Find f(-2)



2) Let g(x)= -x^2+6x+3. Find and simplify g(-4)

     G(-4)=    (simplify answer)


3) Let f(x)= -4x+5. Find f(1/2)


    f(1/2)=      (simplify your answer)




Guest May 18, 2017

1a) Finding f(2) means that you have to substitute 2 for the variable x. So,

      when you substitute, the equation becomes f(2)=-3(2)+7. Then just do the math:

f(2)=-6+7, and then: f(2)=1. Voila!


1b) Just do the same thing: substitute for x, then do the math.

AthenaArtemis  May 18, 2017

14 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.